Gramsci, Croce et le chant X de l’Enfer de Dante - Marcello Mustè (Laboratoire Italien)
Gramsci’s reflections on the Divine Comedy, and more particularly on Canto X of the Inferno, are a decisive moment in his theoretical maturation. Based on a meticulous study of Gramsci’s notes on Dante, his sources and his interlocutors, Marcello Mustè examines, in this chapter from his book Marxismo e filosofia della praxis. Da Labriola a Gramsci (Viella, 2018), both the coded messages – ‘the Cavalcante code’ – associated with his reading of Dante and the theoretical elaboration developed therein. Gramsci’s critique of Benedetto Croce and of the relationship he establishes between structure and poetry enables him to reformulate, through a meditation on Dante’s verses, the problem of the relationship between the aesthetic dimension and the ethical-political dimension, between structure and superstructure. In this context emerges his concept of catharsis, which he would define later as “the starting point for the whole philosophy of praxis”.